Eufemisme sebagai Instrumen Ideologis dalam Wacana Kebijakan Makan Bergizi Gratis - Ulfa Kurniasih; Azizatul Khairi (MIMESIS, 2026)
The Free Nutritious Meal Program (MBG), which was launched on January 6 2025 with an allocation of IDR 71 trillion, is the largest nutritional intervention in Indonesian history. But on March 31, 2026, the government announced a reduction in distribution from six to five days per week—a policy consistently communicated using the phrase "budget adjustment" and its derivatives. This research aims to reveal the euphemistic function of MBG policy diction, identify the ideology that works behind it, and examine its ecotheological implications for food justice and state responsibility. The approach used is Norman Fairclough's three-dimensional Critical Discourse Analysis (AWK)—text, discursive practices, and social practices—with triangulation of four data sources: formal policies (Inpres No. 1/2025, Presidential Decree No. 83/2024), statements by public officials, independent research reports (CISDI, CELIOS, Bappenas, The Indonesian Institute), and national-international media reports. The results of the analysis found seven systematic euphemistic strategies in MBG policy texts: lexical substitution, nominalization that removes the agent, positive word clusters, naturalization of claims, externalization of responsibility, absent presence of beneficiaries, and concealment of contradictions. Behind this strategy, four ideologies work simultaneously: fiscalism as the highest value, centralism without public deliberation, populism without evidence-based evaluation, and unequal distribution of burdens. From an ecotheological perspective, this policy violates the principles of food justice and produces food waste of 1.1–1.4 million tons per year which damages the ecosystem. The research concludes that policy euphemisms are not just a style of language, but rather ideological instruments that reproduce injustice and weaken public accountability.